Penerapan Metode Forward Chaining dan Algoritma Certainty Factor Untuk Mendiagnosa Penyakit Pada Kucing Berbasis Web - Mahreza, Irham Rafi; Fauziah, Fauziah; Natahsia, Novi Dian (STMIK Budi Darma, 2022)
Cats are animals that are very popular today among people, from young people to old people who like cats. We as cat owners must also be responsible for sharing all the needs of the cats we raise. However, many activities and other matters from cat owners also sometimes do not remember to pay attention to the health condition of the cat, so that the cat is susceptible to various diseases. Of the various diseases, generally there are indications that will appear. However, to be able to identify correctly and correctly the type of disease that occurs, of course you need an expert or a veterinarian. On the other hand, the number of veterinarians available is very limited and the number of veterinary clinics is still low. Therefore, it is necessary to build a system that can help diagnose diseases in cats. The purpose of this study is to diagnose early disease in cats to make it easier for cat owners to find out what diseases their pets suffer from with this web-based expert system application. This diagnosis is designed usingmethods Forward Chaining and Certainty Factor. The method Forward Chaining is starting from a set of data that leads to a conclusion. While thealgorithm is Certainty Factor used to calculate the level of confidence from the conclusions of the method Forward Chaining, using PHP programming tools, and Sublime Text 3 and MySQL as databases. From the day of testing the application, there were 250 data with the conclusion that 27 cats (10.8%) were diagnosad with Toxoplasmosis. 79 cats (31.6%) were diagnosad with Cat Flu. 68 cats (27.2%) were diagnosad with Feline Panleukopenia, 46 cats (18.4%) were diagnosad with Cryptococcus and 30 cats (12%) were diagnosad with Feline Infectious Peritonitis.